Five SNPs Within the FGF5 Gene Significantly Affect Both Wool Traits and Growth Performance in Fine-Wool Sheep (Ovis aries) - Zhao, Haiyu; Hu, Ruixue; Li, Fadi; Yue, Xiangpeng (Frontiers in Genetics, 2021)
Fibroblast growth factor 5 (FGF5) gene, a member of fibroblast growth factor superfamily, plays significant roles in the regulation of the hair growth cycle during the development of mammalian hair follicles as well as the skeletal muscle development. In this study, DNA sequencing was used to scan the putative SNPs within the full-length of FGF5 gene, and SNPscan high-throughput technique was applied in the individual genotyping of 604 crossbred sheep. 10 SNPs were identified within FGF5 gene while 5 of them located in intron 1 could be genotyped, namely SNP1 (g. 105914953 G>A), SNP2 (g. 105922232 T>C), SNP3 (g. 105922244 A>G), SNP4 (g. 105922334 A>T) and SNP5 (g. 105922340 G>T). All these SNPs were in accord with the Hardy-Weinberg equilibrium (P>0.05), and displayed the moderate polymorphism with PIC values ranging from 0.302 to 0.374. Thereafter, the correlation analysis between each SNP locus and economic traits including wool length, greasy wool weight and growth performance of sheep was systematically implemented. In our results, SNP1, SNP3, SNP4 and SNP5 were significantly associated with wool length, greasy wool weight and growth traits of SG sheep (P<0.05); SNP1, SNP2, SNP3, and SNP4 were significantly correlated with wool length and growth traits of SSG sheep (P<0.05). Meanwhile, our study revealed a strong linkage disequilibrium (LD) relationship among these SNPs (r2>0.33), except for SNP3 and SNP4 sites (r2=0.30). Combination genotype analysis showed that combination genotypes were significantly associated with mean fiber diameter of SG (P<0.05), and body weight trait of SSG (P<0.01). The above findings suggested that these SNP loci might affect economic traits synergistically and could be regarded as potential molecular markers for improving both wool production and growth performance of fine wool sheep, which lay a molecular foundation for the breeding of fine dual-purpose sheep thereby accelerating the pace of sheep breeding.